2020
DOI: 10.1177/1074248420969571
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-Responsive Antioxidant Nanoparticle Attenuates Whole Body Ischemia/Reperfusion-Induced Multi-Organ Damages

Abstract: Mortality and morbidity after cardiac arrest remain high due to ischemia/reperfusion (I/R) injury causing multi-organ damages, even after successful return of spontaneous circulation. We previously generated H2O2-activatable antioxidant nanoparticles formulated with copolyoxalate containing vanillyl alcohol (PVAX) to prevent I/R injury. In this study, we examined whether PVAX could effectively reduce organ damages in a rat model of whole-body ischemia/reperfusion injury (WBIR). To induce a cardiac arrest, 70µl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For decades, numerous clinical trials have evaluated that oxidative stress plays crucial roles in the occurrence and development of cerebral I/R injury and the impairment of antioxidant defense system including SOD, GSH-Px, and CAT activities endogenously formed by I/R are most applicable 42 - 44 . Naringenin is neuroprotective against a variety of neurological diseases associated with antioxidant mechanisms and inhibition of lipid peroxidation 45 - 47 .…”
Section: Discussionmentioning
confidence: 99%
“…For decades, numerous clinical trials have evaluated that oxidative stress plays crucial roles in the occurrence and development of cerebral I/R injury and the impairment of antioxidant defense system including SOD, GSH-Px, and CAT activities endogenously formed by I/R are most applicable 42 - 44 . Naringenin is neuroprotective against a variety of neurological diseases associated with antioxidant mechanisms and inhibition of lipid peroxidation 45 - 47 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no alteration of intracellular NADPH oxidase 2 activity ( Figure S3 ) [ 34 ]. CPOx nanoparticles treatment systemically showed that there were no adverse reactions induced by the nano formulations in the histology of TUNNEL ( Figure S4 ) [ 35 ]. Biomedical application of the Pox and various CPOx are summarized in Table S1 .…”
Section: Bio Compatibility Of Polyoxalate and Copolyoxalatesmentioning
confidence: 99%